High prevalence of ESBL-producing Klebsiella pneumoniae in clinical samples from central Côte d'Ivoire. (February 2020) - Müller-Schulte, Eloise; Tuo, Marie Nonfra; Akoua-Koffi, Chantal; Schaumburg, Frieder; Becker, Sören L.
Highlights: Multiresistant bacteria pose a significant threat on healthcare systems. There is a lack of data on bacterial resistance patterns from sub-Saharan Africa. Klebsiella pneumoniae strains producing extended spectrum beta-lactamases (ESBL) are highly prevalent in clinical samples from central Côte d'Ivoire. Revised guidelines for the empirical treatment of infections in critically ill patients in Côte d'Ivoire are urgently needed. Abstract: Objectives: Infections caused by multidrug-resistant Enterobacterales pose a significant challenge to clinical patient care, particularly in resource-constrained settings where epidemiological data on antimicrobial resistance are scarce. The aim of this study was to determine the prevalence of extended spectrum beta-lactamase-(ESBL)-producing Klebsiella pneumoniae among clinical samples from a teaching hospital in Bouaké, central Côte d'Ivoire. Methods: Clinical specimens were collected from sterile and non-sterile body sites and were subjected to microbiological diagnostics (April 2016-June 2017). The antimicrobial susceptibility patterns of K. pneumoniae were analysed using automated resistance testing and double-disk diffusion to test for ESBL production. Multiplex PCR was carried out to determine the presence of the resistance-conferring genes bla CTX-M, bla SHV and bla TEM . Results: A total of 107 isolates were included, most of which were obtained from bloodstream (39%; n = 42) and urinary tract infections (39%; n = 42). Among all K. pneumoniae isolates, 84% (n = 90) were ESBL producers, many of which were also not susceptible to sulfonamides (99%), quinolones (81%) and aminoglycosides (79%). The majority of ESBL-producing strains harboured all three investigated bla genes. Conclusion: The high prevalence of ESBL-producing K. pneumoniae in clinical isolates from Côte d'Ivoire calls for revised empirical treatment regimens in critically ill patients with suspected Gram-negative infections, and the establishment of antimicrobial resistance surveillance systems.